Desdobramentos da olimpíada de programação de computadores no desenvolvimento do raciocínio lógico matemático - Pazinato, Ariane Mileidi (2015)
At school, it´s urgent and challenging the reframing and the qualified appropriation of technologies, especially from the recognition that these are constantly present in human life, and its use can be a determining factor for the development of individuals. In this sense, this study aims to verify the development of Computer Programming Olympics for Elementary School Students in the process of mathematical logical reasoning. The before said Olympics is an activity promoted by the Studies and Research in Digital Inclusion Group of the University of Passo Fundo, and consists on challenges to be overcame by the students of sixth to ninth year, of public schools, to be overcame by means of the software of Scratch programming utilization. Methodologically, it is characterized as an investigation with qualitative nature, bolstering up on the participant research and on the focal group, the last one was constituted by students and teachers, members of a competitive team. As instrument to the production of the data were utilized questionnaires, interviews and observation registries. The analysis of the data had as base the theoretical framework, integrates by the constructivism of Papert (1994; 1997; 2007) and Mortari (2001) and by the learning conception proposed by Pozo (2002). Thus, we obtained as main results that Information and Communication Technologies, especially the programming software, can provide new ways of learning, changing the relationship between teachers and students, or between students and students and between students and the knowledge - among this, the mathematician knowledge